Strategic Interactions and Portfolio Choice in Money Management : Evidence from Colombian Pension Funds - Pedraza Morales, Alvaro (World Bank Group, Washington, DC, 2014)
This paper studies the portfolio choice of strategic fund managers in the presence of a peer-based underperformance penalty. Evidence is taken from the Colombian pension fund management industry, where six asset managers are in charge of portfolio allocation for the mandatory contributions of the working population. These managers are subject to a peer-based underperformance penalty, known as the Minimum Return Guarantee. The trading behavior by the managers is studied before and after a change in the strictness of the guarantee in June 2007. The evidence suggests that a tighter minimum return guarantee results in more trading in the direction of peers, a behavior that is more pronounced for underperforming managers. These managers rebalance their portfolios by buying securities in which they are underexposed relative to their peers, as opposed to selling assets in which they are overexposed. Overall, the results suggest that incentives for managers to be close to industry benchmarks play an important role in the portfolio allocation of these funds.